2005
DOI: 10.1001/archsurg.140.7.656
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Technetium Tc 99m Sestamibi SPECT Imaging in the Management of Primary Hyperparathyroidism in Patients With Concomitant Multinodular Goiter

Abstract: Preoperative parathyroid and thyroid imaging using technetium Tc 99m sestamibi scintigraphysingle-photon emission computed tomography (Tc 99m MIBI SPECT) and technetium Tc 99m sodium pertechnetate, respectively, in patients with parathyroid adenomas and concomitant multinodular goiters enables the selection of those suitable for minimally invasive radioguided surgery. Design: One hundred thirty patients with primary hyperparathyroidism were treated surgically during a 30month period. Forty-one of these 130 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 21 publications
(25 reference statements)
0
23
0
4
Order By: Relevance
“…Most authors agree to define 99m Tc-sestamibi scintigraphy as the most powerful preoperative diagnostic tool in PHPT, and it has undoubtfully been responsible for the changes in therapeutic strategies [7]. Even more, the accuracy of 99m Tc-sestamibi scintigraphy can be increased with the addition of some techniques, and ultrasound, the double tracer subtraction technique with 99m Tc-pertechnectate, and the single photon emission technique (SPECT) are the most frequently reported [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree to define 99m Tc-sestamibi scintigraphy as the most powerful preoperative diagnostic tool in PHPT, and it has undoubtfully been responsible for the changes in therapeutic strategies [7]. Even more, the accuracy of 99m Tc-sestamibi scintigraphy can be increased with the addition of some techniques, and ultrasound, the double tracer subtraction technique with 99m Tc-pertechnectate, and the single photon emission technique (SPECT) are the most frequently reported [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy of dual-phase scintigraphy combined with ultrasonography has been found to be superior to that of other scintigraphic or radiological techniques (10,11). Studies comparing planar imaging and single photon emission computed tomography (SPECT) have shown significantly increased sensitivity for Tc-99m sestamibi SPECT, thus supporting its routine use prior to surgery (12)(13)(14).…”
mentioning
confidence: 99%
“…The technical aspects of SPECT appear to be superior in comparison to planar imaging. 12,26,37 There are, however, reports that the proof of a parathyroid adenoma with concomitant large nodular goiter was not possible with SPECT. 12 Furthermore, Norman et al, who mainly used planar imaging as their method of proof, reported a sensitivity of 100% to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…12,26,37 There are, however, reports that the proof of a parathyroid adenoma with concomitant large nodular goiter was not possible with SPECT. 12 Furthermore, Norman et al, who mainly used planar imaging as their method of proof, reported a sensitivity of 100% to be achieved. 14 Several studies have shown that a combination of ultrasound and MIBI nuclear scan improved the sensitivity of locating adenoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation